On Rate of Convergence of Jungck-Type Iterative Schemes - Nawab Hussain; Vivek Kumar; Marwan A. Kutbi (Abstract and Applied Analysis)
We introduce a new iterative scheme called Jungck-CR iterative scheme and study the stability and strong convergence of this iterative scheme for a pair of nonself-mappings using a certain contractive condition. Also, convergence speed comparison and applications of Jungck-type iterative schemes will be shown through examples.